Empire Of The Wolves - Nahon, Chris; Jover, Arly.; David Kammenos; Didier Sauvegrain; Jocelyn Quivrin; Laura Morante; Philippe Bas; Jean Reno (France Kairos, 2005)
When the young detective Paul Nerteaux (Jocelyn Quivrin) finds the third slashed female corpse of illegal Turkish immigrants, he decides to ask for support to the experienced dark retired detective Jean-Louis Schiffer (Jean Reno) to chase the serial killer. Together, they infiltrate in the Turkish mafia trying to find the answer to the crimes. Meanwhile, the worker Anna Heymes (Arly Jover) is being submitted to a brain treatment and has severe headaches and glimpses of memories and visions. When these two parallel events collide, disclose that the Turkish organization "The Wolves" is behind them.
Luc Bossi
Language(s): English, French Subtitle(s): English, French
Keywords: Drama; Thriller; Action